Comparação de dois diferentes métodos de aplicação de sistemas adesivos para cimentação de pinos de fibra de vidro em condutos radiculares - Zambon, Mateus [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
Observando as dificuldades existentes para se obter uma boa adesão em um tecido muito complexo como o conduto radicular, a criação de um protocolo efetivo se faz necessário para que o clínico alcance melhores resultados durante a cimentação de pinos de fibra de vidro no conduto radicular. Assim o objetivo do estudo 1 foi avaliar o efeito dos métodos de aplicação dos sistemas adesivos condiciona-e-lava (AS) ou universal (SU), com escovas manuais (MB) ou escovas para condutos acionados mecanicamente (RB), associados aos cimentos resinosos convencionais Relyx ARC (RA) ou Relyx Ultimate (RU) sobre a resistência de união e extensão de tags formados, na dentina radicular dos terços cervical, médio e apical do espaço preparado para pino. Quarenta raízes de incisivos bovinos conóides foram tratadas endodonticamente. Após o preparo radicular para pino, as raízes foram divididas em 4 grupos, de acordo com os métodos de aplicação do sistema adesivo e protocolo de cimentação de pinos de fibra. Após 6 meses, espécimes dos terços cervical, médio e apical do espaço para pino foram submetidos a avaliação da resistência de união, em máquina de ensaio eletromecânica, e mensuração da extensão de tags formados. Os dados obtidos foram analisados pelos testes de ANOVA e Tukey (α=.05). RB-AS-RA e RB-SU-RU demonstraram os maiores valores de resistência de união nos terços cervical e médio do espaço para pino (P< 0.05), mas no terço apical os valores foram similares entre si (P > 0.05). MB-SU-RU demonstrou a menor extensão de tags no substrato dentinário, independentemente do terço do espaço para pino (P < 0.05). O método de aplicação do sistema adesivo com escovas para conduto proporciona maior resistência de união do protocolo de cimentação e extensão de tags na dentina dos terços cervical e médio do espaço para pino. O objetivo do estudo 2 foi avaliar os efeitos dos modos de aplicação de sistemas adesivos universais Scotchbond Universal (SU) e Ambar Universal (AM), com aplicadores manuais (MB) ou escova rotativa (RB) durante a cimentação de pinos de fibra de vidro com os cimentos Relyx Ultimate(RU) e Allcem Core (AC) na resistência de união e modo de falha nos terços cervical, médio e apical dos pinos. Quarenta dentes bovinos foram tratados endodonticamente e preparados para cimentação de pinos de fibra de vidro. Os corpos de prova foram distribuídos aleatoriamente em 4 grupos (n = 10), de acordo com o modo de aplicação do adesivo universal, na estratégia etch-and-rinse, e o sistema de cimentação utilizado. Após a cimentação, foi realizado o teste de resistência de união por push-out nos diferentes terços do espaço do pino. O modo de falha também foi analisado. ANOVA de duas vias e teste de Tukey foi usado (α=5%). Independentemente do terço pós-espaço o uso de escova rotativa aumentou a resistência de união do Scotchbond Universal quando comparado aos grupos que utilizaram Ambar Universal. Nos terços cervical e médio, apresentaram maior incidência de falha adesiva tipo 2 e falha mista, no terço apical apresentaram maior incidência de falhas coesivas. A aplicação do sistema adesivo Scotchbond Universal com escova rotativa tem efeito positivo com o protocolo de cimentação com Relyx Ultimate.

Observing the existing difficulties to obtain a good adhesion in a very complex tissue such as the root canal, the creation of an effective protocol is necessary for the clinician to achieve better results during the cementation of fiberglass posts in the root canal. Thus, the objective of study 1 was to evaluate the effect of the application methods of the condition-and-lava (AS) or universal (SU) adhesive systems, with manual brushes (MB) or mechanically actuated conduit brushes (RB), associated with cements. conventional resin composites Relyx ARC (RA) or Relyx Ultimate (RU) on the bond strength and extension of formed tags in the root dentin of the cervical, middle and apical thirds of the post-prepared space. Forty roots of conoid bovine incisors were endodontically treated. After root preparation for post, the roots were divided into 4 groups, according to the application methods of the adhesive system and fiber post cementation protocol. After 6 months, specimens from the cervical, middle and apical thirds of the pin space were submitted to evaluation of bond strength, in an electromechanical testing machine, and measurement of the extent of formed tags. The data obtained were analyzed by ANOVA and Tukey tests (α=.05). RB-AS-RA and RB-SU-RU showed the highest values of bond strength in the cervical and middle thirds of the post space (P< 0.05), but in the apical third the values were similar to each other (P > 0.05). MB-SU-RU demonstrated the smallest extent of tags on the dentin substrate, regardless of the post space third (P < 0.05). The method of application of the adhesive system with brushes for conduit provides greater bond strength of the cementation protocol and extension of tags in the dentin of the cervical and middle thirds of the post space. The aim of study 2 was to evaluate the effects of application modes of Scotchbond Universal (SU) and Ambar Universal (AM) universal adhesive systems, with manual applicators (MB) or rotary brush (RB) during the cementation of fiberglass posts. with Relyx Ultimate(RU) and Allcem Core (AC) cements on bond strength and failure mode in the cervical, middle and apical thirds of the posts. Forty bovine teeth were endodontically treated and prepared for cementation of fiberglass posts. The specimens were randomly distributed into 4 groups (n = 10), according to the way of application of the universal adhesive, in the etch-and-rinse strategy, and the cementation system used. After cementation, a push-out bond strength test was performed in the different thirds of the post space. The failure mode was also analyzed. Two-way ANOVA and Tukey's test were used (α=5%). Regardless of the post space third, the use of a rotating brush increased the bond strength of Scotchbond Universal when compared to groups that used Ambar Universal. In the cervical and middle thirds, they presented a higher incidence of type 2 adhesive failure and mixed failure, in the apical third they presented a higher incidence of cohesive failures. The application of the Scotchbond Universal Adhesive System with a rotating brush has a positive effect with the cementation protocol with Relyx Ultimate.Observing the existing difficulties to obtain a good adhesion in a very complex tissue such as the root canal, the creation of an effective protocol is necessary for the clinician to achieve better results during the cementation of fiberglass posts in the root canal. Thus, the objective of study 1 was to evaluate the effect of the application methods of the condition-and-lava (AS) or universal (SU) adhesive systems, with manual brushes (MB) or mechanically actuated conduit brushes (RB), associated with cements. conventional resin composites Relyx ARC (RA) or Relyx Ultimate (RU) on the bond strength and extension of formed tags in the root dentin of the cervical, middle and apical thirds of the post-prepared space. Forty roots of conoid bovine incisors were endodontically treated. After root preparation for post, the roots were divided into 4 groups, according to the application methods of the adhesive system and fiber post cementation protocol. After 6 months, specimens from the cervical, middle and apical thirds of the pin space were submitted to evaluation of bond strength, in an electromechanical testing machine, and measurement of the extent of formed tags. The data obtained were analyzed by ANOVA and Tukey tests (α=.05). RB-AS-RA and RB-SU-RU showed the highest values of bond strength in the cervical and middle thirds of the post space (P< 0.05), but in the apical third the values were similar to each other (P > 0.05). MB-SU-RU demonstrated the smallest extent of tags on the dentin substrate, regardless of the post space third (P < 0.05). The method of application of the adhesive system with brushes for conduit provides greater bond strength of the cementation protocol and extension of tags in the dentin of the cervical and middle thirds of the post space. The aim of study 2 was to evaluate the effects of application modes of Scotchbond Universal (SU) and Ambar Universal (AM) universal adhesive systems, with manual applicators (MB) or rotary brush (RB) during the cementation of fiberglass posts. with Relyx Ultimate(RU) and Allcem Core (AC) cements on bond strength and failure mode in the cervical, middle and apical thirds of the posts. Forty bovine teeth were endodontically treated and prepared for cementation of fiberglass posts. The specimens were randomly distributed into 4 groups (n = 10), according to the way of application of the universal adhesive, in the etch-and-rinse strategy, and the cementation system used. After cementation, a push-out bond strength test was performed in the different thirds of the post space. The failure mode was also analyzed. Two-way ANOVA and Tukey's test were used (α=5%). Regardless of the post space third, the use of a rotating brush increased the bond strength of Scotchbond Universal when compared to groups that used Ambar Universal. In the cervical and middle thirds, they presented a higher incidence of type 2 adhesive failure and mixed failure, in the apical third they presented a higher incidence of cohesive failures. The application of the Scotchbond Universal Adhesive System with a rotating brush has a positive effect with the cementation protocol with Relyx Ultimate.
Comparison of two different methods of application of adhesive systems for cementation of fiberglass posts in root canals
Keywords: Adesivos; Cimentos dentários; Técnica para retentor intrarradicular; Cimentos de resina; Adhesives; Dental cements; Post and core technique; Resin cements